Portage and Path Dependence * - Bleakley, Hoyt; Lin, Jeffrey (Quarterly Journal of Economics, 2012)
Many cities in North America formed at obstacles to water navigation, where continued transport required overland hauling or portage . Portage sites attracted commerce and supporting services, and places where the falls provided water power attracted manufacturing during early industrialization. We examine portage sites in the U.S. South, Mid-Atlantic, and Midwest, including those on the fall line , a geomorphological feature in the southeastern United States marking the final rapids on rivers before the ocean. Although their original advantages have long since become obsolete, we document the continuing importance of historical portage sites. We interpret these results as path dependence and contrast explanations based on sunk costs interacting with decreasing versus increasing returns to scale.